Dynamical behavior of the Family of cubic functions - Mizal H. Alobaidi; Murtada M. Alkazraji (Tikrit Journal of Pure Science)
May R.M. gave the example of the family of cubic maps of the interval . Rogers T. D. extends the analysis of May beyond that region . “